Musashi-2 Deficiency Triggers Colorectal Cancer Ferroptosis by Downregulating the MAPK Signaling Cascade to Inhibit HSPB1 Phosphorylation - Xiaole Meng; Xiao Peng; Wanxin Ouyang; Hui Li; Risi Na; Wenting Zhou; Xuting You; Yuhuan Li; Xin Pu; Ke Zhang; Junjie Xia; Jie Wang; et al. (Biological Procedures Online, 2023)
Abstract Background Musashi-2 (MSI2) is a critical RNA-binding protein (RBP) whose ectopic expression drives the pathogenesis of various cancers. Accumulating evidence suggests that inducing ferroptosis of tumor cells can inhibit their malignant biological behavior as a promising therapeutic approach. However, it is unclear whether MSI2 regulates cell death in colorectal cancer (CRC), especially the underlying mechanisms and biological effects in CRC ferroptosis remain elusive. Methods Experimental methods including qRT‒PCR, immunofluorescence, flow cytometry, western blot, co-immunoprecipitation, CCK-8, colony formation assay, in vitro cell transwell migration and invasion assays, in vivo xenograft tumor experiments, liver and lung CRC metastasis models, CAC mice models, transmission electron microscopy, immunohistochemistry, histopathology, 4D label-free proteomics sequencing, bioinformatic and database analysis were used in this study. Results Here, we investigated that MSI2 was upregulated in CRC and positively correlated with ferroptosis inhibitor molecules. MSI2 deficiency suppressed CRC malignancy by inhibiting cell proliferation, viability, migration and invasion in vitro and in vivo; and MSI2 deficiency triggered CRC ferroptosis by changing the intracellular redox state (ROS levels and lipid peroxidation), erastin induced cell mortality and viability, iron homeostasis (intracellular total irons and ferrous irons), reduced glutathione (GSH) levels and mitochondrial injury. Mechanistically, through 4D-lable free proteomics analysis on SW620 stable cell lines, we demonstrated that MSI2 directly interacted with p-ERK and MSI2 knockdown downregulated the p-ERK/p38/MAPK axis signaling pathway, which further repressed MAPKAPK2 and HPSB1 phosphorylation, leading to decreased expression of PCNA and Ki67 and increased expression of ACSL4 in cancer cells. Furthermore, HSPB1 could rescue the phenotypes of MSI2 deficiency on CRC ferroptosis in vitro and in vivo. Conclusions This study indicates that MSI2 deficiency suppresses the growth and survival of CRC cells and promotes ferroptosis by inactivating the MAPK signaling pathway to inhibit HSPB1 phosphorylation, which leads to downregulation of PCNA and Ki67 and upregulation of ACSL4 in cancer cells and subsequently induces redox imbalance, iron accumulation and mitochondrial shrinkage, ultimately triggering ferroptosis. Therefore, targeted inhibition of MSI2/MAPK/HSPB1 axis to promote ferroptosis might be a potential treatment strategy for CRC.